(Unmet) Standards for emotional support and their short- and medium-term consequences. Issue 2 (2nd April 2016) - Joseph, Andrea; Afifi, Tamara D.; Denes, Amanda
ABSTRACT: The purpose of this study is to explore the effects of emotional support discrepancy (ESD), or the degree to which people feel their standards for emotional support are met, immediately after a supportive interaction and in the days following the interaction. One hundred thirteen dating couples discussed in the laboratory a topic that was stressful for one of the partners and then completed daily diary logs for seven days. Immediately following the laboratory interaction, a smaller ESD was indirectly associated with more positive affect, less negative affect, and greater relationship satisfaction through cognitive reappraisal. In the days following the laboratory interaction, ESD was not associated with future conversations about either the laboratory stressor or stressors that emerged during the week, but was marginally and positively associated with brooding rumination about the laboratory stressor and positively associated with brooding rumination about the partner's support in general. In addition, both types of rumination were associated with less positive affect, more negative affect, and less relationship satisfaction over the course of the week.